Assessment of Disease Progression in Idiopathic and Collagen Vascular ILDs Using Spirometry, DLCO, and 6 Minute-Walk-Test - Rawul, Sindhoora; Rawul, Apoorva; Singaraju, Saikrishna; Kumar, R. Vijai; Chelluri, Srinivasa I. (International Journal of Integrated Health Sciences, 2025)
Background: Monitoring progression in interstitial lung diseases is essential for timely intervention, with spirometry, DLCO, and 6MWT serving as key functional tests.Objectives: To evaluate disease progression in idiopathic and collagen vascular interstitial lung diseases (ILD) using pulmonary function parameters, including spirometry, DCLO (Diffusing Capacity of the Lungs for Carbon Monoxide), and the six-minute walk test.Methods: This prospective observational study was performed from January  2023 to December 2024 at Shadan Institute of Medical Sciences , Hyderabad, India. In this study, the pulmonary function in 51 ILD patients were assessed using spirometry, DLCO, and the six-minute walk test. Patients underwent detailed clinical evaluation, routine investigations, chest X-ray, ABG analysis, and HRCT to confirm ILD. Those suspected of CTD-ILD had RF and ANA testing, with a complete ANA profile if positive. Subjects were categorized into IPF and CTD-ILD groups. Pulmonary parameters were compared, and standard treatments were administered. Six deaths occurred during follow up period.  For statistical purposes p value less than 0.05 was taken as statistically significant.Results: Fifty-one patients with diffuse parenchymal lung disease were included, with idiopathic pulmonary fibrosis (IPF) (46.4%) and connective tissue disease-associated ILD (CTD-ILD) (44.6%) as the main types. The CTD-ILD patients were younger (mean age 48.64 vs. 61.80 years, p=0.0006) and predominantly female. IPF patients had lower six-minute walk distance (239.73 vs. 312.60 meters, p=0.0066) and SpO2. Strong correlations were observed between lung function parameters in both groups. However, 6MWT showed no correlation in CTD-ILD.Conclusion: In ILD patients, FVC and DLCO were found to be reliable for disease monitoring, while simpler tests like 6MWT and FVC proved to be useful in resource-limited settings. Further research is needed to confirm their role in tracking IPF progression and treatment response.